Crystal structure of the SarR protein from Staphylococcus aureus - Liu, Yingfang (The National Academy of Sciences, 2001)
The expression of virulence determinants in Staphylococcus aureus is controlled by global regulatory loci (e.g., sarA and agr). The sar (Staphylococcus accessory regulator) locus is composed of three overlapping transcripts (sarA P1, P3, and P2, transcripts initiated from the P1, P3, and P2 promoters, respectively), all encoding the 124-aa SarA protein. The level of SarA, the major regulatory protein, is partially controlled by the differential activation of the sarA promoters. We previously partially purified a 13.6-kDa protein, designated SarR, that binds to the sarA promoter region to down-modulate sarA transcription from the P1 promoter and subsequently SarA expression. SarR shares sequence similarity to SarA, and another SarA homolog, SarS. Here we report the 2.3 Å-resolution x-ray crystal structure of the dimeric SarR-MBP (maltose binding protein) fusion protein. The structure reveals that the SarR protein not only has a classic helix–turn–helix module for DNA binding at the major grooves, but also has an additional loop region involved in DNA recognition at the minor grooves. This interaction mode could represent a new functional class of the “winged helix” family. The dimeric SarR structure could accommodate an unusually long stretch of ≈27 nucleotides with two or four bending points along the course, which could lead to the bending of DNA by 90° or more, similar to that seen in the catabolite activator protein (CAP)–DNA complex. The structure also demonstrates the molecular basis for the stable dimerization of the SarR monomers and possible motifs for interaction with other proteins.